Strategi dan Metode Mengajar Anak Remaja Milenial - Tobi, Ongki Riando; Bubu, Yuliana; Salmon, Radela; Sagala, Lenda Dabora JF (Jurnal Kala Nea, 2023)
Adolescence is a period of transition from childhood to maturity, this term indicates that the initial period from puberty to maturity. Then the millennial generation is those born in 1980-2000, it should be noted that this generation is considered special from the previous generation, especially with regard to technology. Then the word strategy comes from the Latin strategya, which is defined as the art of using plans to achieve goals, and in general the method is a regulated method that is carried out to achieve certain goals. The purpose of this study is to describe strategies and methods for teaching millennial children. The research method used in this study is a qualitative research method. Because each generation always changes according to the times, therefore the author uses a qualitative method, because this method is very appropriate for use in the process of data collection and data processing.